Bata Primavera Sdn. Bhd. / Mohd Danial Arieff Mohd Ghafoor … [et al.] - MOHD GHAFOOR, MOHD DANIAL ARIEFF; ISMAIL, PUTERI NADHIRAH; MOHD SHUKRI, SYARIZAD SOFIA; RAHMAN, FATHIIN NABIILAH; NOR WAHID, FARRAH KHALIDAH (2019)
This report is to study the performances and the ways of operation for the local shoes company where an interview was done at Bata shop located at Seksyen 7, Shah Alam. There are three main perspective that being study in this report including the success of the company, design challenge and strategy implementation. Furthermore, this reports will explain details on history of company, financial, management of the organization, technology used and also the current marketing strategy. This report also focus on the analysis of strengths, weaknesses, opportunities and threat that affecting the company itself. Furthermore, the consumer trend canvas are also being discussed in details. The problems of the company were found out and then the solution given after the brainstorming process. Some recommendations being proposed for the improvement of the operations that is ideal for the increasing Bata's needs, and increase the corporate image as the multinational retailer of worldwide brand.